2008
DOI: 10.1111/j.1533-2500.2008.00177.x
|View full text |Cite|
|
Sign up to set email alerts
|

Sympathetic Blocks: The Evidence

Abstract: The sympathetic nervous system has been implicated in numerous pain syndromes ranging from neuropathic pain to vascular pain to visceral pain. In light of this, sympathetic ganglia have been the target of local anesthetic blockade to determine the sympathetic role in the transmission of pain. If analgesia is afforded with local anesthetic blockade, chemical or thermal neurolysis have been utilized to attempt to provide long-term relief. Despite frequent use of minimally invasive sympathetic blocks and neurolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
97
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 75 publications
1
97
1
4
Order By: Relevance
“…In a study by Ansari et al [53], 95% of patients with facial pain at the beginning of the study reported significant improvement after the study. The facial pain effect size observed in our study (d = 0.96) was much higher than that estimated from Young et al's data (d = 0.51), likely due to the application of multimodal frequencies (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80) Hz and 1 MHz) in the AxioSonic system. Our effect size for quality of life measures using the SNOT-22 questionnaire (d = 0.45) was lower than Young et al's paper [40] (d = 0.9).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In a study by Ansari et al [53], 95% of patients with facial pain at the beginning of the study reported significant improvement after the study. The facial pain effect size observed in our study (d = 0.96) was much higher than that estimated from Young et al's data (d = 0.51), likely due to the application of multimodal frequencies (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80) Hz and 1 MHz) in the AxioSonic system. Our effect size for quality of life measures using the SNOT-22 questionnaire (d = 0.45) was lower than Young et al's paper [40] (d = 0.9).…”
Section: Discussioncontrasting
confidence: 55%
“…The SPG is involved in tissue inflammation, lacrimation, mucus production and other parasympathetic processes [71][72][73][74]. Low frequency neurostimulation (20 Hz, much lower than ultrasound frequencies) of the SPG or the Vidian nerve leads to vasodilation and associated inflammation [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…Second line drugs indicated for limited situations are steroids and other anticonvulsants and antidepressants. Sympathetic block is one of the commonest options 7 and more promising results are obtained the earlier the blockade is induced 8 . For upper limbs CRPS (UULL), stellate ganglion blockade is indicated 9 and is aimed at decreasing pain and functionally improving the affected limb.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, paravertebral ganglia are involved in many physiological and pathological aspects of neuropathic, vascular, visceral pain syndromes, the Raynaud's syndrome and hyperhydrosis. Several interventions on ganglia-surgical and chemical sympathectomy, the ganglion block, and chemical or thermal sympatholysis are applied as a possible treatment for pathological conditions [2]. The stellate ganglion block decreases the cerebral vascular tone for relieving cerebral vasospasm [4].…”
Section: Introductionmentioning
confidence: 99%